2018
DOI: 10.1159/000493724
|View full text |Cite
|
Sign up to set email alerts
|

International Survey on the Management of Acute Kidney Injury and Continuous Renal Replacement Therapies: Year 2018

Abstract: Introduction: Definition, prevention, and management of acute kidney injury (AKI) and the optimal prescription and delivery of renal replacement therapy (RRT) are currently matters of ongoing discussion. Due to the lack of definitive published literature, a wide gap might exist between routine clinical practice and available recommendations. The aim of this survey was to explore the clinical approach to AKI and RRT in a broad population of nephrologists and intensivists participating in the 36th International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 17 publications
(23 reference statements)
4
21
2
2
Order By: Relevance
“…Our subjects use almost equally high (≥250 mg/day) and low doses of Furosemide (≤250 mg/day) in the conservative treatment of AKI, and a relatively equal representation in the range of up to 30.0% of AKI patients requiring CRRT is reported. These results are different from last year's study in which it was stated that most use high doses in oligurian patients and that 13.0% of patients require CRRT (5). In our institutions, most respondents stated that they use the KDIGO 2 criterion for "early" start of CRRT, and for already present complications associated with AKI or poor response to conservative therapy, participants start CRRT "late".…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Our subjects use almost equally high (≥250 mg/day) and low doses of Furosemide (≤250 mg/day) in the conservative treatment of AKI, and a relatively equal representation in the range of up to 30.0% of AKI patients requiring CRRT is reported. These results are different from last year's study in which it was stated that most use high doses in oligurian patients and that 13.0% of patients require CRRT (5). In our institutions, most respondents stated that they use the KDIGO 2 criterion for "early" start of CRRT, and for already present complications associated with AKI or poor response to conservative therapy, participants start CRRT "late".…”
Section: Discussioncontrasting
confidence: 78%
“…Over the past year, 33% reported that 21-40% of the patients had "early" onset CRRT recovery in renal function and 46.8% said that less than 5.0% of the patients had died, as opposed to "late" CRRT onset which reported an increase in renal function <5.0% out of 44.7% of the participants, whereas 40.4% reported death in 5.0%-20% of the patients (Table 1). According to the results, slightly more than half of the participants still use the RIFLE criteria to define the AKI, while in terms of representation, the following use the KDIGO criteria, which is different from the results published last year, in which the KDIGO criteria are dominant (5). The higher prevalence of the RIFLE classification has been reported in previous studies, and in our sample it can be explained by the participation of nonnephrological specialty respondents and possibly by a high percentage of physicians with many years of experience who are somewhat skeptic about accepting novelties (6,7).…”
Section: Resultscontrasting
confidence: 59%
“…However, data from practice surveys in 2014 and 2018 indicate heparin was commonly used for CRRT as the anticoagulant of choice [19,20] (83-42%, respectively) but is possibly reducing in favor of citrate and will be compared further in a proposed 1,450 patient, randomized controlled trial in Germany [18].…”
Section: Introductionmentioning
confidence: 99%
“…Eine systemische Antikoagulation ist bei kontinuierlichen Nierenersatzverfahren in aller Regel notwendig. Als Standard gilt unfraktioniertes Heparin [233,234]. Die gerinnungshemmende Wirkung wird dabei hauptsächlich über Bindung an Antithrombin induziert.…”
Section: Zeitpunkt Modalität Und Antikoagulation Für Eine Nierenersaunclassified